Prevalence of Gastrointestinal Parasites in Yaks of Lehe VDC, Manaslu Conservation Area - Byanju, Reena; Shrestha, SP; Khanal, DR (Nepal Journal of Science and Technology, 2012)
Qualitative analysis of 44 fecal samples of yaks from Lehe VDC of Manaslu Conservation Area showed the positive result in 36 samples (81.82%). Strongyle showed the highest infection (47.23%) while the least was with Amphistomum (8.34%). Infection with Trichuris, Ascaris, Eimeria and Coccyx were also reported in the present study. The pattern of infection was both mixed (52.78%) and single (47.23%). DOI: http://dx.doi.org/10.3126/njst.v12i0.6525 Nepal Journal of Science and Technology 12 (2011) 366-369